2010
DOI: 10.1016/j.eurpsy.2010.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The First Step in the Validation of a new Screen for Violence Risk in Acute Psychiatry: The Inpatient Context

Abstract: Despite promising results further validation studies are required before the V-RISK-10 is adopted into routine clinical practise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 23 publications
1
52
1
Order By: Relevance
“…The amount of violently behaving female patients was lower in the present study than in the previous studies. The proportion of violent female patients range from one third (Daffern et al 2003) to similar proportions of male and female patients, which are reported from Norway (Hartvig et al 2010), Canada (Nicholls et al 2009) and Australia (Daffern et al 2003) in the forensic settings. Furthermore, the proportion of violent female patients was higher in the elderly study in Norway; 4 out of 10 of the violently behaving patients were female (Almvik et al 2006), and in a study of general psychiatric patients; one third of the physically violent patients were female (Ogloff & Daffern 2006).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The amount of violently behaving female patients was lower in the present study than in the previous studies. The proportion of violent female patients range from one third (Daffern et al 2003) to similar proportions of male and female patients, which are reported from Norway (Hartvig et al 2010), Canada (Nicholls et al 2009) and Australia (Daffern et al 2003) in the forensic settings. Furthermore, the proportion of violent female patients was higher in the elderly study in Norway; 4 out of 10 of the violently behaving patients were female (Almvik et al 2006), and in a study of general psychiatric patients; one third of the physically violent patients were female (Ogloff & Daffern 2006).…”
Section: Discussionmentioning
confidence: 57%
“…) to similar proportions of male and female patients, which are reported from Norway (Hartvig et al . ), Canada (Nicholls et al . ) and Australia (Daffern et al .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the Violence Risk–10 items (V‐Risk 10; Hartvig, Roaldset, Moger, Ostberg, & Bjørkly, ) was developed in Norway as a brief structured clinical risk assessment screen for inpatient violence. Evidence suggests that the V‐Risk 10 is accurate in predicting in‐patient violence and was found to be easy and quick to use (Hartvig et al, ).…”
Section: Recent Developments In Short‐term Violence Risk Assessmentmentioning
confidence: 99%
“…The purpose of screening is to initially cast a wide net in identifying those who pose a risk to others (Hartvig, Roaldset, Moger, Østberg, & Bjørkly, 2011). This is helpful in referring those identified in screening as high risk for further in-depth assessment.…”
Section: Introductionmentioning
confidence: 99%